Analisis kompetensi budaya dalam meningkatkan kemampuan Bahasa Inggris - Nurhayati, Dwi (Maliki Interdisciplinary Journal, 2024)
This article aims to analyze the role of cultural competence in improving English language skills. This article finds that cultural competence is essential in improving English language skills, especially in the face of globalization and the need for mastery of the English language. In this article, cultural competence is defined as the ability to understand and apply different cultural values in a variety of situations. The results showed that having better cultural competence in developing English language skills, especially in dealing with cultural differences that occur in the language process. Therefore, this study recommends that having good cultural competence to improve English language skills and face the increasingly complex challenges of globalization.